"When there is a book to stick to": teacher professionalism and manual-based programmes in two Swedish early childhood education settings. Issue 1 (2nd January 2021) - Bartholdsson, Åsa
ABSTRACT: With focus on teachers' experiences and understandings of manual-based programmes, this article explores the implications for teacher professionalism. It locates teachers' use of manual-based programmes in the intersection of two currents of ideas in contemporary society and within education: therapy culture and the evidence movement. The article builds on material from interviews with teachers and participant-observation in a kindergarten and a preschool class in the Swedish educational system where programmes for the development of children's social and emotional learning were used – programmes developed by external expertise, claiming the programmes to have a solid evidence base. These were initially implemented from above in the educational system, but as shown, embraced from within professional culture as means to perform a therapeutic ethos and to guide professional conduct. This article shows that, in working with the programmes and its exercises, teacher's own professional knowledge and judgement, rather than that of the external expertise, are questioned in an act of subordination to the programme manuals. Hence, a twice devalued professionalism, externally (from above) as well as internally (from within), emerges through the interviews and the observations.